Management of Acute Complications during Endovascular Procedures in Peripheral Arterial Disease: A Review - Kumar, Ajay Pawan; Valakkada, Jineesh; Ayappan, Anoop; Kannath, Santhosh (Journal of Clinical Interventional Radiology ISVIR, 2022)
Endovascular therapy, as opposed to surgical bypass, has become the mainstay for peripheral arterial disease even in long segment occlusions. Complications can occur during the arterial access, catheter manipulation, balloon dilation, and/or stent placement. Given the high prevalence of comorbidities such as diabetes, hypertension, renal dysfunction, and coronary artery disease in these patients, early identification of procedural complications and initiation of treatment are of paramount importance. This review aims to provide comprehensive data on the identification and management of commonly encountered endovascular complications during endovascular interventions in peripheral arterial disease.
Keywords: pseudoaneurysm; complications; femoral artery access